Transformasi Pembelajaran Bahasa Inggris melalui Teknologi Artificial Intelligence (AI) di SMA Islam Al-Kamal Sarang Rembang - Siti Rosyidah (Institut Agama Islam Hidayatullah Batam, 2025)
This research analyzes the transformation of learning using Artificial Intelligence (AI) applications in English language learning at Al-Kamal Islamic High School in Rembang. The objectives of this study include the implementation of AI application utilization, student responses, obstacles, and its impact on motivation and learning outcomes. The method used is descriptive qualitative thru observation, interviews, questionnaires, and documentation. The research results show that applications like Grammarly, Chat GPT, Elsa Speak, and Duo lingo help improve grammar, speaking, pronunciation, vocabulary, and writing skills, and learning motivation increased from 60% to 85%. Constraints include limited devices, unstable networks, low digital literacy, and teacher training. Nevertheless, AI remains effective and viable for use as an innovative modern learning strategy at the school level. Therefore, it is hoped that the school can respond well and serve as a reference in modern, effective, and innovative learning transformation at the school level.